Impact of caffeine intake on female basketball players` performance - Nieto-Acevedo, R.; García-Sánchez, C.; Bravo-Sánchez, A.; Abián-Vicén, J.; Abián, P.; Portillo, J.; Martínez-Rubio, C.; Calvo, J. L.; Diaz-Lara, J. (Nutrients, 2025)
Background: This study aimed to analyze the effect of caffeine ingestion on basketball performance in semi-professional female players.